Protective Effects of Vitamin E on Chemotherapy-Induced Peripheral Neuropathy: A Meta-Analysis of Randomized Controlled Trials - Miao, Huikai; Li, Rongzhen; Chen, Dongni; Hu, Jia; Chen, Youfang; Xu, Chunmei; Wen, Zhesheng (Annals of nutrition and metabolism, 2021)
Chemotherapy-induced peripheral neuropathy (CIPN) is a common symptom, but prophylactic measures cannot still be carried out effectively. In addition, the efficacy of vitamin E in preventing peripheral neurotoxicity caused by chemotherapy is inconclusive. Therefore, we collected the relevant randomized controlled trials (RCTs) and performed a meta-analysis to examine whether the vitamin E has a positive effect in CIPN. We searched PubMed, EMBASE, Cochrane, and other databases in December 2019 for eligible trials. Two reviewers conducted the analysis independently when studies were homogeneous enough. Eight RCTs, involving 488 patients, were identified. Upon pooling these RCTs, patients who received vitamin E supplementation of 600 mg/day had a lower incidence of CIPN (risk ratio [RR] 0.31; 95% confidence interval [CI] 0.14-0.65; p = 0.002) than the placebo group. Vitamin E played a key role in decreasing the incidence of peripheral neuropathy in the cisplatin chemotherapy group (RR 0.28; 95% CI 0.14-0.54; p = 0.0001). Moreover, vitamin E supplementation significantly decreased patients' sural amplitude after 3 rounds of chemotherapy (RR -2.66; 95% CI -5.09 to -0.24; p = 0.03) in contrast with that of placebo supplementation, while no significant difference was observed when patients were treated with vitamin E after 6 rounds of chemotherapy. In addition, the vitamin E-supplemented group had better improvement in the neurotoxicity score and lower incidence of reflexes and distal paraesthesias than the control group. Available data in this meta-analysis showed that vitamin E supplementation can confer modest improvement in the prevention of CIPN.